Enhancing energy sector sustainability through robust green governance mechanisms for carbon neutrality - Bashir Mikail Usman; Satirenjit Kaur Johl; Parvez Alam Khan (Discover Sustainability)
Abstract This study examines the adoption of green governance systems in Nigeria's energy sector to attain carbon neutrality, following Sustainable Development Goals (SDGs) 7 and 13. The study conducted conducts a comprehensive narrative review of the literature to examine the current status of Nigeria's energy transition, emphasizing renewable sources such as solar, wind, hydro, and biofuel. It underscores stakeholder engagement for efficient collaboration and underlines the implementation of Green Governance (GG) strategies to enhance the performance of energy companies to achieve carbon neutrality. The proposed Climate Governance Framework (CG-GD) seeks to direct the industry towards a worldwide green deal. The findings highlight the essential function of green governance in transforming economic growth, innovating sustainable technologies, and fostering enduring socio-economic and environmental advantages in Nigeria. This paper examines the knowledge gap regarding Nigeria's sustainability practices, providing theoretical and practical insights for managers, regulators, policymakers, and other stakeholders.